2004
DOI: 10.1177/0020872804034138
|View full text |Cite
|
Sign up to set email alerts
|

International Fieldwork Experience

Abstract: Twenty-five US schools provided international field experience either in agencies dealing with international problems or in foreign countries. There appear to be two primary patterns for making overseas placements. One is through the initiative of a faculty member and the other is through the learning centers in different countries. Students chose field experiences in foreign countries because they were enthusiastic about it. Also, some of them had family, friends or relatives in those countries. The largest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…A study of twenty-five social work schools in the USA has shown that students' enthusiasm is a significant factor in undertaking international placements, though the financial factor appears to be the most common one deterring students from undertaking such (Rai, 2004;NuttmanShwartz and Berger, 2012). Students' learning is said to be relatively better when they are placed in teams (Pawar et al, 2004;Das and Anand, 2014) and also when they utilise appropriate values and adequately resolve value conflicts (Furman, 2001;Lough, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study of twenty-five social work schools in the USA has shown that students' enthusiasm is a significant factor in undertaking international placements, though the financial factor appears to be the most common one deterring students from undertaking such (Rai, 2004;NuttmanShwartz and Berger, 2012). Students' learning is said to be relatively better when they are placed in teams (Pawar et al, 2004;Das and Anand, 2014) and also when they utilise appropriate values and adequately resolve value conflicts (Furman, 2001;Lough, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A high level of planning and administrative support often places strain on the resources of schools of social work and faculty. Some social work programmes have established and maintain ongoing relationships with international partners to facilitate and support international study options (Rai, 2004) and a small number of programmes have reciprocal arrangements which supports the movement of students and staff in both directions (Kreitzer et al, 2009;Saunders et al, 2012). Panos et al, (2004) reported that the most active international social work programmes demonstrated a high level of commitment to developing and maintaining relationships in the overseas host institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, the need for onsite support, debriefing and supervision is highlighted (Kreitzer et al, 2009;Larson & Allen, 2006;Nuttman-Shwartz & Berger, 2012;Rai, 2004). Both formal and informal support was considered central to the outcomes for students (Pawar et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Language is typically a core issue when dealing with international social work because many international practicums involve non-native students going to a placement in a country whose language is different from their own (Rai, 2004). This is particularly problematic when trying to give students the opportunity to provide direct practice to local and indigenous populations.…”
Section: Languagementioning
confidence: 99%